MOLLUSCS FROM THE UPPER MESOPHOTIC ZONE IN A SCARCELY KNOWN REEF OF THE WESTERN EQUATORIAL ATLANTIC: Moluscos da zona mesofótica superior de um recife pouco conhecido do Atlântico Equatorial Ocidental - Barroso, Cristiane Xerez; Freitas, João Eduardo Pereira de; Spotorno, Paula; Tâmega, Frederico Tapajós de Souza; Franklin Júnior, Wilson; Matthews-Cascon, Helena (Arquivos de Ciências do Mar, 2021)
Despite the increasing focus on biodiversity of mesophotic coral ecosystems (MCEs) on a global scale, some biological groups, such as molluscs, are still poorly investigated. The taxonomic diversity of the molluscan fauna of a scarcely known MCE of the Western Equatorial Atlantic, Northeastern Brazil, was surveyed. Samples were collected along the shallower strata of the upper mesophotic zone (between 33-36 m depth). Twenty-one taxa (nine species of gastropods, ten species of bivalves, and two taxa of chitons) were listed, two of which (Novastoa sp. and Thylaeodus sp.) are potential endemic species. A new northern limit of distribution of Persicula moscatellii was established and seven species had new bathymetric records for living specimens (Barbatia domingensis, Barbatia cancellaria, Lamychaena hians, Leiosolenus bisulcatus, Pinctada imbricata, Hipponix incurvus, and Persicula moscatellii). Hipponix costellatus are the most representative species with 49 individuals, followed by Lima caribaea with six individuals. The present work is the first contribution to the knowledge of the molluscan fauna associated with consolidated substrates from this little-known MCE. Keywords: mesophotic coral ecosystems, tropical reef, molluscan diversity, Brazilian Province, conventional SCUBA.